A legalidade e efetividade dos atos judiciais realizados por inteligência artificial - Pereira, Thiago Pedroso (2020)
Artificial Intelligence is a reality, and its applicability has been gaining more and more space over the years and human relations being approached by cyber means. From the moment of its conception, AI, as it is also known, has perceived application opportunities in the most diverse fields of knowledge, not seeing any barriers or impediments due to its ability to achieve results that until then could only be achieved with human effort. , of a specialist nature. Nevertheless, the intersection between Law and Artificial Intelligence, has been shown to be procrastinated, much in view of the lack of adaptability of its professionals and agents to the use of technological means to carry out legal conduct. Despite the little use of AI by the law, the Brazilian Judiciary is showing itself more and more accustomed to the use of this technology in its structure. Whether for carrying out administrative acts or for judicial acts. As it will be treated throughout this dissertation, the use of AI is no longer something imaginary for those who are fond of films of an imaginative scientific nature, and becomes an important element in the planning of the Judiciary with regard to rendering judicial acts, in an assisted or individualized manner supported in initiatives by the State Courts, the National Council of Justice and the Superior Courts. The objective of this work will be to demonstrate not only the legality and effectiveness of the acts practiced by an AI, but also to debate elements about the possibility of using it as a substantial and qualitative tool for judicial acts as well as in the exercise of possible support in the process of elaboration of lawsuits. decisions. For this, materials were collected regarding the use of AI in the news portals of the courts, international cases, websites specialized in law and artificial intelligence and the few works that address the issues together.